OPTIMALISASI PERAWATAN ALAT-ALAT KESELAMATAN SEBAGAI PENUNJANG KESELAMATAN AWAK KAPAL DI KN. BIMA SAKTI - Firdaus Sitepu (Dinamika Bahari, 2017)
As for target of writing of this handing out is to know optimalization treatment of safety appliance as supporter safety of crew man in KN. Bima Sakti. Pursuant to the target, hence this handing out take title " Optimalization Treatment of Appliance Safety As Supporter Safety of Crew Man In Kn. Bima Sakti". Method weared by writer in writing this handing out is descriptive method. As for research obyek is KN. Bima Sakti. Method data collecting use field study, Bibliography study (research library) and documentation. Pursuant to result of research which have been conducted, hence can be taken by some conclusion that is things causing safety appliance do not function in an optimal fashion moment used in training in KN Bima Sakti is because lack of the understanding of hitting procedure treatment of real correct safety appliance pursuant to regulation of treatment of safety appliance according to Solas (Safety Of Life Sea at) and because lack of facility equipments of treatment to safety appliance given by company so that activity of treatment become less maximal. Things related to execution to be is optimal of treatment of safety appliance better in KN Bima Sakti is with treatment of lifeboat, benefactor raft ( liferaft), benefactor float ( lifebuoy), benefactor clothes ( jacket life) executed by inspection periodical to safety appliance like weekly periodic inspection, monthly and annual according to procedure regulation of Solas (Safety Of Life Sea at), and also inspection of equipments of safety appliance is also checked by the parts of the safety appliance accurately and detail as according to tables of checklist inspection of safety appliance. method Treatment of safety appliance, because method treatment of safety appliance as base from make-up of efficiency in is optimal of activity from safety appliance on board so that the safety appliance can be used in an optimal fashion by all crew man if happened emergency on board.